Systematic review of optical coherence tomography usage in the diagnosis and management of basal cell carcinoma. (27th October 2015) - Cheng, H.M.; Guitera, P.
Summary: Optical coherence tomography (OCT) is a noninvasive imaging tool used in vivo in real time for diagnosis, treatment delineation and monitoring of basal cell carcinoma (BCC). Features of BCC on OCT have been widely described and reviewed. However, the diagnostic accuracy of OCT in these various applications is unclear. We systematically reviewed the literature to assess the accuracy of OCT in diagnosis and management of BCC using the Embase and Medline databases. In total 179 unique references were identified in the initial search, of which 22 studies with 556 histologically proven BCCs were eligible. Assessment of the quality of eligible studies was undertaken using the STROBE criteria. Data extraction and quality assessment were performed independently by the two authors. This systematic review provides an overview of the clinical applications of OCT in the diagnosis and management of BCC. OCT has been suggested to be useful in the diagnosis, treatment planning and treatment monitoring of BCC. As the technology improves and its utility increases, further studies with good methodological quality will be needed to implement OCT into daily practice. Abstract : What's already known about this topic? Optical coherence tomography (OCT) can be used in diagnosis, treatment planning and treatment monitoring in basal cell carcinoma (BCC). Features of BCC on OCT have been described. What does this study add? This study examines the current literature to elicit the diagnostic accuracy of OCT when used in these various indications. It provides recommendations for the use of OCT in BCC diagnosis and treatment and facilitates its implementation in daily practice.